2020
DOI: 10.1016/j.taap.2020.115237
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of drug combinations used in COVID-19 treatment: in silico toxicogenomic data-mining approach

Abstract: Improvement of COVID-19 clinical condition was seen in studies where combination of antiretroviral drugs, lopinavir and ritonavir, as well as immunomodulant antimalaric, chloroquine/hydroxychloroquine together with the macrolide-type antibiotic, azithromycin, was used for patient's treatment. Although these drugs are “old”, their pharmacological and toxicological profile in SARS-CoV-2 – infected patients are still unknown. Thus, by using in silico toxicogenomic data-mining approach, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…On the other hand, some of the drugs, like Lopinavir, induced CCL2 mRNA expression and protein secretion, CCL3 protein expression, IL1B mRNA expression, IL6 protein expression and secretion. Similarly, Atazanavir increased CCL2 and CCL3 protein expression, while Ritonavir increased IL6 mRNA expression, protein expression and secretion, CCL2 protein expression and secretion, as well as CCL3 protein expression [89] . Conclusively, several identified drugs (lopinavir, ritonavir, atazanavir) may increase secretion of pro‐inflammatory cytokines, which might aggravate cytokine storm.…”
Section: Resultsmentioning
confidence: 85%
“…On the other hand, some of the drugs, like Lopinavir, induced CCL2 mRNA expression and protein secretion, CCL3 protein expression, IL1B mRNA expression, IL6 protein expression and secretion. Similarly, Atazanavir increased CCL2 and CCL3 protein expression, while Ritonavir increased IL6 mRNA expression, protein expression and secretion, CCL2 protein expression and secretion, as well as CCL3 protein expression [89] . Conclusively, several identified drugs (lopinavir, ritonavir, atazanavir) may increase secretion of pro‐inflammatory cytokines, which might aggravate cytokine storm.…”
Section: Resultsmentioning
confidence: 85%
“…As BCL2L1 is the most important hub gene in the autophagy interaction network, the importance of BCL2L1 was further highlighted in this study. Baralić et al evaluated the safety of drug combinations for COVID-19 treatment using an in silico toxicogenomic data-mining approach, and found that the drug combination of chloroquine and azithromycin affected the expression of BCL2L1 in vivo [ 37 ]. Moreover, Liu et al reported that matrine could reduce COVID-19 with liver damage by increasing the expression of BCL2L1 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…В другом исследовании была оценена безопасность комбинаций лекарственных препаратов, используемых для лечения COVID-19 [75], методом сбора токсикогеномных данных, чтобы понять профиль безопасности двух выбранных стратегий лечения COVID-19: ритонавир/лопинавир и хлорохин/гидроксихлорохин + азитромицин. Использовались доступные базы данных, предсказавшие молекулярные механизмы побочных реакций.…”
Section: кардиотоксичность препаратов применяемых для лечения Covid-19unclassified